(untitled) (diségno, 2020)
Drawing and measure are two fundamental words for the field of representation. Both can have two different meanings: one concerning their instrumental use, the other referring to their finalizations. As to the cosmic harmony called into question by this topic, I would like to say that it is an objective of great importance and extent, but also very generic and difficult to define. I will, therefore, start from definitions that permit me to specify the scope of application of the terms I will be using. Further on I will be more explicit. (read more)